Using Wearable Devices to Enhance Executive Functioning in Students with Learning Disabilities - Dr. Mohammad Abedrabbu Alkhawaldeh; Mohamad Ahmad Saleem Khasawneh (Migration Letters, 2023)
The present investigation sought to explore the efficacy of wearable devices in augmenting executive functioning abilities among students who experience learning disabilities. The individuals involved in this study were assigned in a random manner to either the experimental group, which consisted of 30 participants receiving a wearable device intervention, or the control group, which consisted of 30 participants receiving standard support. The findings of the study revealed noteworthy enhancements in executive functioning measures among the participants assigned to the experimental group, as compared to those in the control group. These improvements were evident through a reduction in scores on the Behavior Rating Inventory of Executive Function (BRIEF), indicating a decrease in executive function-related behavioral difficulties. Additionally, the experimental group exhibited higher scores on both the Tower of Hanoi test and the Digit Span task, suggesting an enhanced ability to plan and problem-solve, as well as an improved working memory capacity. Although there were no significant variations in academic performance observed among the different groups, the results of this study shed light on the promising prospects of utilizing wearable devices to enhance executive functioning abilities in students who face learning disabilities. Additional investigation is imperative to delve into the enduring ramifications and extrapolate the outcomes to a more expansive cohort.